TAX AVOIDANCE, FIRM SIZE, AND LEVERAGE: Evidence From Indonesia Listed Companies - Mariana, Citra (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to reveal firm size and leverage on tax avoidance in the Consumer Goods Industry Sector Companies Listed on the Indonesia Stock Exchange in 2016-2018. The method used in this study is explanatory. This research was conducted on data in the form of financial statements. To analyze the research data, multiple linear regression analysis was used. Based on the results of multiple linear regression analysis, it shows that firm size has no influence on tax avoidance in the Consumer Goods Industry Sector Companies Listed on the Indonesia Stock Exchange in 2016-2018. Leverage influence tax avoidance in the Consumer Goods Industry Sector Companies Listed on the Indonesia Stock Exchange in 2016-2018